Prokaryotic Cell Wall Compounds Structure and Biochemistry - König, Helmut; Claus, Harald; Varma, Ajit.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Microbial cell wall structures play a significant role in maintaining cells’ shape, as protecting layers against harmful agents, in cell adhesion and in positive and negative biological activities with host cells. All prokaryotes, whether they are bacteria or archaea, rely on their surface polymers for these multiple functions. Their surfaces serve as the indispensable primary interfaces between the cell and its surroundings, often mediating or catalyzing important interactions. Prokaryotic Cell Wall Compounds summarizes the current state of knowledge on the prokaryotic cell wall. Topics concerning bacterial and archaeal polymeric cell wall structures, biological activities, growth and inhibition, cell wall interactions and the applications of cell wall components, especially in the field of nanobiotechnology, are presented.
Cell Wall Polymers and Structures of Bacteria -- The Murein Sacculus -- Occurrence, Structure, Chemistry, Genetics, Morphogenesis, and Functions of S-Layers -- Bacterial Polysaccharide Capsules -- Lipopolysaccharides -- Structure, Biosynthesis, and Function of Teichoic Acids and Related Cell Wall Glycopolymers in the Gram-positive Cell Envelope -- Outer Membrane Proteins -- Cell Wall Polymers and Structures of Archaea -- Cell Envelopes of Methanogens -- The Cell Envelopes of Haloarchaea: Staying in Shape in a World of Salt -- Cell Envelopes of Crenarchaeota and Nanoarchaeota -- Biological Activities -- Immunochemistry of the Cell Walls of Methanogenic Archaea: A View from the Past into the Future -- Cell Wall Structure and Pathogenicity -- Cell Wall Growth and Inhibition -- Cell Wall Targeted Antibiotics -- Bacterial Autolysins -- Cell Wall Interactions -- Prokaryotic Cell–Cell Interaction -- Adhesion of Bacteria to Protists -- Application of Cell Wall Components -- Prokaryotic Cell Wall Components: Structure and Biochemistry -- Accumulation of Heavy Metals by Micro-organisms: Biomineralization and Nanocluster Formation.
Keywords: Microbiology; Biochemistry; Cell biology; Immunology; Medical microbiology; Microbiology; Biochemistry, general; Cell Biology; Immunology; Medical Microbiology